Chondroprotectors in theraphy of osteoarthritis - Zupanets, I; Zimin, S (Annals of Mechnikov’s Institute, 2020)
Osteoarthritis (ОА) is a multifactorial disease associated with age, which is characterized by high polymorbidity, level of disability and death. In elderly patients with OA pain therapy especially related to factors such as a significant decrease in physical activity, the presence of comorbid disease (mainly heart disease) and complications caused by irrational drug therapy. Available in an elderly patient OA various somatic diseases and a wide range of treatments used for their medicines suggest the choice of individual treatment strategy that takes into account the ratio of the alleged benefits and possible risks of the purpose of each drug funds in favor of the most safe and effective therapy.